2023
DOI: 10.1186/s12888-023-04645-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of studies exploring prevalence of non-specific anxiety in undergraduate university students

Abstract: Background Anxiety is a common mental health problem in the general population, and is associated with functional impairment and negative impacts upon quality of life. There has been increased concern about university students’ mental health in recent years, with a wide range of non-specific anxiety rates reported worldwide in undergraduate university students. We aimed to explore prevalence of non-specific anxiety in undergraduate university student populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…Only one systematic review included two studies with diagnostic interviews. 1 A French study based on data from the WHO Composite International Diagnostic Interview -Short Form (CIDI) collected in 2005––2006 found 12 months prevalence of major depressive disorder, anxiety disorder and substance use disorder to be 8.9%, 15.7% and 8.1% respectively. 2 A Chinese study based on data from the WHO CIDI 3.0 collected in 2007 found lifetime, 12-month and 30-day prevalence of neurotic disorders to be 25.6%, 15.7% and 6.8% respectively.…”
mentioning
confidence: 99%
“…Only one systematic review included two studies with diagnostic interviews. 1 A French study based on data from the WHO Composite International Diagnostic Interview -Short Form (CIDI) collected in 2005––2006 found 12 months prevalence of major depressive disorder, anxiety disorder and substance use disorder to be 8.9%, 15.7% and 8.1% respectively. 2 A Chinese study based on data from the WHO CIDI 3.0 collected in 2007 found lifetime, 12-month and 30-day prevalence of neurotic disorders to be 25.6%, 15.7% and 6.8% respectively.…”
mentioning
confidence: 99%
“…Previous systematic reviews and meta-analyses spanning 17 and 40 years, respectively, have shown that the prevalence of anxiety symptoms among undergraduate students worldwide ranges from 34.8-39.65%, with 19.1% and 10.3% having mild anxiety and severe anxiety, respectively [19,20]. Anxiety symptoms may diminish a student's attention, memory, and learning effectiveness; affect self-esteem and socialization, contribute to psychological stress and isolation, and may promote additional health problems as a result of chronic psychological stress [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Karademas’s [ 15 ] ideas about common and specific predictors of well-being and ill-being, this study aimed to explore whether and which perfectionism traits are uniquely related to either well-being or stress, indicating their specific predictive role, or whether they are related to both of them, indicating their common and simultaneous roles in well-being promotion and ill-being protection. This may help in the optimization of psychological interventions in the higher education context, suggesting parsimonious and effective psychological targets [ 16 ].…”
Section: Introductionmentioning
confidence: 99%